Study of Viscosity and Density Changes of Waste Cooking Oil Biodiesel Due to Gradual Heat Treatment - Dani Hari Tunggal Prasetiyo; Andi Sanata; Robertus Sidartawan; Muhammad Trifiananto; Asroful Abidin; Linda Kurnia Supraptiningsih (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2025)
Biodiesel from used cooking oil is a renewable fuel for diesel engines that has the potential to be developed as a substitute for fossil fuels. However, the physical properties of biodiesel such as viscosity and density are affected by heat treatment. This will certainly affect engine performance, combustion quality and diesel engine efficiency. This study aims to analyze the heat treatment of used cooking oil biodiesel in stages with temperature values of 40°C, 50°C, 60°C, 70°C, and 80°C. Biodiesel is obtained from used cooking oil by a synthesis process using transesterification with ethanol and KOH catalyst. The results of the study were the viscosity and density values of used cooking oil biodiesel. The results showed that heat treatment of biodiesel reduced the viscosity and density values. The viscosity value continued to decrease along with the increase in the heating value from 4.52 cSt to 2.84 cSt. For the density value also decreased from 867 kg/m³ to 827 kg/m³. This study shows that heat treatment on biodiesel before use has the potential to improve atomization characteristics and fuel flow rates, so that combustion efficiency and diesel engine performance can be optimal.